Implementasi Peraturan Menteri Pertanian Republik Indonesia Nomor 98/Permentan/Ot.140/9/2013 di Kabupaten Rokan Hulu Riau - Kadaryanto, Bagio; Rani, Nabella Puspa (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2018)
Objectives to be achieved in this research isexplaining about the implementation of business licensing the cultivation of oil palm plantations by the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 98/PERMENTAN/OT.140/9/2013;Describes the implementation of business licensing the cultivation of oil palm plantations in Rokan Hulu; as well as formulate and explain the measures to be taken by the Government of Rokan Hulu to regulate business licensing cultivation of oil palm plantations in Rokan Hulu. The specific targets to be achieved in this research is theorderly implementation of licensing the cultivation of palm oil plantation in Rokan Hulu with better and more effective. So it does not cause environmental problems derived from oil palm plantations in Rokan Hulu. Type of research is a sociological law that is more focused on the implementation of business licensing the cultivation of oil palm plantations by the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 98/PERMENTAN/OT.140/9/2013, the problems that arise regarding the implementation of business licensing cultivation oil palm plantations in Rokan Hulu. Results and discussion of this research are the implementation of business licensing the cultivation of oil palm plantations in Rokan Hulu has not been fully implemented by the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 98/PERMENTAN/OT.140/9/2013.